GMAT Question of the Day - Daily to your Mailbox; hard ones only

 It is currently 19 Feb 2019, 23:24

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

## Events & Promotions

###### Events & Promotions in February
PrevNext
SuMoTuWeThFrSa
272829303112
3456789
10111213141516
17181920212223
242526272812
Open Detailed Calendar
• ### Free GMAT Prep Hour

February 20, 2019

February 20, 2019

08:00 PM EST

09:00 PM EST

Strategies and techniques for approaching featured GMAT topics. Wednesday, February 20th at 8 PM EST

February 21, 2019

February 21, 2019

10:00 PM PST

11:00 PM PST

Kick off your 2019 GMAT prep with a free 7-day boot camp that includes free online lessons, webinars, and a full GMAT course access. Limited for the first 99 registrants! Feb. 21st until the 27th.

# What is the value of F(-1)-F(1)?

Author Message
TAGS:

### Hide Tags

GMATH Teacher
Status: GMATH founder
Joined: 12 Oct 2010
Posts: 750
What is the value of F(-1)-F(1)?  [#permalink]

### Show Tags

10 Feb 2019, 18:13
00:00

Difficulty:

65% (hard)

Question Stats:

36% (01:39) correct 64% (01:29) wrong based on 22 sessions

### HideShow timer Statistics

GMATH practice exercise (Quant Class 14)

What is the value of F(-1)-F(1)?

(1) F(x) = x^2 , for all x
(2) F(x+1) = F(x) + 2x + 1, for all x

_________________

Fabio Skilnik :: GMATH method creator (Math for the GMAT)
Our high-level "quant" preparation starts here: https://gmath.net

Math Expert
Joined: 02 Aug 2009
Posts: 7334
Re: What is the value of F(-1)-F(1)?  [#permalink]

### Show Tags

10 Feb 2019, 18:40
fskilnik wrote:
GMATH practice exercise (Quant Class 14)

What is the value of F(-1)-F(1)?

(1) F(x) = x^2 , for all x
(2) F(x+1) = F(x) + 2x + 1, for all x

So we are looking for $$F(-1)-F(1)$$.

(1) $$F(x) = x^2$$ , for all x
We can get the value of F(-1) and F(1), so sufficient
$$F(-1) = (-1)^2=1$$
$$F(1) = (1)^2=1$$
so $$F(-1)-F(1)=1-1=0$$
Sufficient

(2) $$F(x+1) = F(x) + 2x + 1$$, for all x
The difference of 1 in x and x+1 should tempt you to rearrange and work on the variables accordingly..
Now F(-1) and F(1) have difference of 1-(-1) or 2, so let us work in similar fashion..
$$F(x+1) = F(x) + 2x + 1......... F(x)-F(x+1) = -( 2x + 1)$$
a) let x = -1, so $$F(x)-F(x+1) = -( 2x + 1)......F(-1)-F(-1+1) = -( 2(-1) + 1)=-(-1)=1$$, that is F(-1)-F(0) = 1
b) let x = 0, so $$F(x)-F(x+1) = -( 2x + 1)......F(0)-F(0+1) = -( 2(0) + 1)=-(1)=-1$$, that is F(0)-F(1) = -1
Add the two colored equation F(-1)-F(0)+ F(0)-F(1) = 1+ (-1)..........
so $$F(-1)-F(1)=1-1=0$$
Sufficient

D
_________________

1) Absolute modulus : http://gmatclub.com/forum/absolute-modulus-a-better-understanding-210849.html#p1622372
2)Combination of similar and dissimilar things : http://gmatclub.com/forum/topic215915.html
3) effects of arithmetic operations : https://gmatclub.com/forum/effects-of-arithmetic-operations-on-fractions-269413.html
4) Base while finding % increase and % decrease : https://gmatclub.com/forum/percentage-increase-decrease-what-should-be-the-denominator-287528.html

GMAT Expert

Manager
Joined: 09 Jun 2014
Posts: 240
Location: India
Concentration: General Management, Operations
Schools: Tuck '19
Re: What is the value of F(-1)-F(1)?  [#permalink]

### Show Tags

10 Feb 2019, 21:58
fskilnik wrote:
GMATH practice exercise (Quant Class 14)

What is the value of F(-1)-F(1)?

(1) F(x) = x^2 , for all x
(2) F(x+1) = F(x) + 2x + 1, for all x

This approach is really good and I got struck at the highlighted point.

Here is my approach.The main concern is statement 2

1.F(x) = x^2 , for all x

F(-1) = x^2 = 1
F(1)= x^2 = 1

So we have F(-1) - F(1)= 0

2.
F(x+1) = F(x) + 2x + 1, for all x ---------------------- Main equation

Now my line of thinking was:Lets get F(-1) so I did x+1=-1 which gave x=-2.
Now substituting in main equation 2

F(-2+1)= F(-2) + 2*(-2) +1

=> F(-1) = F(-2) - 4 + 1
=F(-2) -3

I think this is wrong step,I identified a little later.

We should rather take X=-1 directlly ,this will save us from getting F(-2) and have equation in F(0) form thereby saving us from other variable.

so substituing X=-1 in main equation

F(0) = F(-1) + 2*-1 +1
= F(-1) - 1 ---------------------------------- 1

Again to get F(1) Lets make x+1= 1 ,X=0
Now again substituting in main equation 2

F(1) = F(0) + 2*0 + 1
=F(0) + 1 --------------------2
implies

F(0) = F(1)-1

Substituting F(0) in equation 1

F(1)-1 = F(-1) - 1

Rearranging

F(-1) - F(1) = 0

Hence sufficient.

Hope it helps!!
GMATH Teacher
Status: GMATH founder
Joined: 12 Oct 2010
Posts: 750
Re: What is the value of F(-1)-F(1)?  [#permalink]

### Show Tags

11 Feb 2019, 09:28
fskilnik wrote:
GMATH practice exercise (Quant Class 14)

What is the value of F(-1)-F(1)?

(1) F(x) = x^2 , for all x
(2) F(x+1) = F(x) + 2x + 1, for all x

$$? = F\left( { - 1} \right) - F\left( 1 \right)$$

$$\left( 1 \right)\,\,F\left( x \right) = {x^2}\,,\,\,{\rm{for}}\,\,{\rm{all}}\,\,x\,\,\,\, \Rightarrow \,\,\,\,F\left( x \right) = F\left( { - x} \right)\,,\,\,{\rm{for}}\,\,{\rm{all}}\,\,x\,\,\,\,\mathop \Rightarrow \limits^{x\, = \,1} \,\,\,\,\,F\left( 1 \right) = F\left( { - 1} \right)\,\,\,\,\,\, \Rightarrow \,\,\,\,\,\,? = 0$$

$$\left( 2 \right)\,\,F\left( {x + 1} \right) - F\left( x \right) = 2x + 1\,,\,{\rm{for}}\,\,{\rm{all}}\,\,x\,\,\,\left( * \right)$$

$$\left. \matrix{ {\rm{Take}}\,\,x = - 1\,\,\,\,\,\mathop \Rightarrow \limits^{\left( * \right)} \,\,\,\,\,F\left( 0 \right) - F\left( { - 1} \right) = - 2 + 1\,\,\, \hfill \cr {\rm{Take}}\,\,x = 0\,\,\,\,\,\mathop \Rightarrow \limits^{\left( * \right)} \,\,\,\,\,F\left( 1 \right) - F\left( 0 \right) = 1 \hfill \cr} \right\}\,\,\,\,\,\mathop \Rightarrow \limits^{\left( + \right)} \,\,\,\,\,F\left( 1 \right) - F\left( { - 1} \right) = 1 + \left( { - 2 + 1} \right) = 0\,\,\,\,\, \Rightarrow \,\,\,\,\,? = - 0 = 0$$

The correct answer is therefore (D).

We follow the notations and rationale taught in the GMATH method.

Regards,
Fabio.
_________________

Fabio Skilnik :: GMATH method creator (Math for the GMAT)
Our high-level "quant" preparation starts here: https://gmath.net

Re: What is the value of F(-1)-F(1)?   [#permalink] 11 Feb 2019, 09:28
Display posts from previous: Sort by